The smart grid as a security device: Electricity infrastructure and urban governance in Kingston and Rio de Janeiro. (December 2021) - Pilo', Francesca
This article aims to contribute to recent debates on the politics of smart grids by exploring their installation in low-income areas in Kingston (Jamaica) and Rio de Janeiro (Brazil). To date, much of this debate has focused on forms of smart city experiments, mostly in the Global North, while less attention has been given to the implementation of smart grids in cities characterised by high levels of urban insecurity and socio-spatial inequality. This article illustrates how, in both contexts, the installation of smart metering is used as a security device that embeds the promise of protecting infrastructure and revenue and navigating complex relations framed along lines of socio-economic inequalities and urban sovereignty – here linked to configurations of state and non-state (criminal) territorial control and power. By unpacking the political workings of the smart grid within changing urban security contexts, including not only the rationalities that support its use but also the forms of resistance, contestation and socio-technical failure that emerge, the article argues for the importance of examining the conjunction between urban and infrastructural governance, including the reshaping of local power relations and spatial inequalities, through globally circulating devices.